Statistics poster challenge for schools. (19th June 2012) - Payne, Brad; Freeman, Jenny; Stillman, Eleanor
Abstract The analysis and interpretation of data are important life skills. A poster challenge for schoolchildren provides an innovative outlet for these skills and demonstrates their relevance to daily life. We discuss our Statistics Poster Challenge and the lessons we have learned.